Lean New Product Development in Business Games: A Case Study - SHENG, WANTING (2019)
With the increasing market demand and customers’ requirements, business games are getting popular for training and education applications among academics and practitioners. Academics and practitioners are demanding ‘bespoke’ or made to order (MTO) games that best suited their applications. Hence, there are challenges for business games developers to develop games in shorter times and at lower costs. This research studied the application Lean thinking in business games new product development (NPD). The research aims to: (1) understand the challenges of MTO business games; (2) identify wastes in the business game NPD process; and (3) propose a Lean NPD stages for business games. This study adopted a case study approach for data collection and analysis. Data was collected from a local Nottingham business gaming firm over a period of 6 months (under an apprenticeship program). Data from over two MTO business games was collected and analyzed. The findings showed six major wastes and three management issues in the existing MTO business games processes. Suggestions for eliminating the wastes and management issues, and a streamlined Lean NPD for business gaming were proposed. CEOs of the case firm were delighted with the findings and agreed that the proposed approach could help the firm to be more agile and competitive.